Show that 3 tan-1x = tan-1(3x-x3)/(1-3x2)

Solution:

We know that tan-1A + tan-1B = tan-1(A+B)/(1-AB)

LHS = 3 tan-1x

= tan-1x + tan-1x + tan-1x

= tan-1(2x/(1-x2)) + tan-1x

= tan-1[(2x/(1-x2)) + x]/[(1- 2x.x/(1-x2)]

= tan-1(3x-x3)/(1-3x2)

= RHS

Hence proved.

Was this answer helpful?

 
   

5 (3)

(2)
(0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question